PEMBERDAYAAN SISWA DIFABEL MELALUI KEWIRAUSAHAAN SOSIAL BERBASIS KEARIFAN LOKAL DI GUNUNG KIDUL YOGYAKARTA - Umi Yuliati; Warto Warto; Tiwuk K. Hastuti; Waskito Widi Wardojo; Isnaini W. Wardani; Insiwi F. Setiasih; M. Bagus Sekar Alam (Jurnal Abdi Insani, 2023)
This service will help foster an entrepreneurial spirit based on the local potential for children with disabilities in Ngawen Gunung Kidul Regency, Yogyakarta. The development of self-reliance that leads to the provision of pottery-making skills packaged in the concept of social entrepreneurship is expected to revive the enthusiasm of children with disabilities to be independent. This service activity aligns with the government's program on empowering children with disabilities as stipulated in Law No. 8 of 2016. The partner of this service is SLB Sutawijaya who has dedicated himself for 18 years in educating children with disabilities. The purpose of this service is to increase the number of students with disabilities who are independent, skilled, care about each other and the surrounding environment, and participate in preserving pottery as a local potential by applying the concept of social entrepreneurship. In the implementation of this activity using the method of observation, discussion, operational work, and direct assistance. The dedication begins with submitting several proposed activities, managing time, and distributing work together with the board of the institution. After the team prepares and carries out activities together, the social media design is handed over to partners to continue as a provision for online promotion. This service activity will do several things, including HR management including hospitality, discussions with teachers, and student conditioning. At the production stage, activities include making pottery using printing tools, and pottery finishing techniques. Promotional activities are carried out through exhibitions, bazaars, and accounts on social media. All activities are carried out in stages with an approach that is fun for students. The output of the community service activities is that students have a caring spirit for others and the environment, can make pottery products, and perform pottery finishing techniques. In this service, training is also provided for creating online media and holding exhibitions of original works to help promote pottery products. He also makes activity videos, promotional media through print or online media, and scientific publications in the Nationally accredited journal Sinta 3. This service will help foster an entrepreneurial spirit based on local potential for children with disabilities in Ngawen Gunung Kidul District, Yogyakarta. The development of self-reliance that leads to the provision of pottery-making skills packaged in the concept of social entrepreneurship is expected to revive the enthusiasm of children with disabilities to be independent. This dedication is in line with the government's program on empowering children with disabilities as stipulated in Law No. 8 of 2016 and according to the Regulation of the State Minister for Women's Empowerment and Child Protection of the Republic of Indonesia Number 10 of 2011 concerning education service policies for Children with Special Needs (ABK). In this service, it is proven that pottery-making training can increase the number of students with disabilities who are independent, skilled, care about each other and the surrounding environment, and help preserve the existence of pottery as a local potential by applying the concept of social entrepreneurship.